Menjaga Standar Kualitas Pelayanan Guest Service Agent dengan PDCA pada Masa New Normal: Studi Kasus sebuah Hotel di Uluwatu, Bali - Putu Arin Melia Nugrahani; Ida Ayu Sri Puspa Adi; Putu Gede Eka Darmaputra (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
This research was conducted to determine how the strategy of maintaining the quality standards of Guest Service Agent services in the new normal era in Uluwatu. Interview techniques and documentation obtain data. The data analysis in this study is descriptive and qualitative by describing the interview results from the front office manager and guest service supervisor at Hotel based on documentation data in the form of guest comment reviews on OTA (Online Travel Agent) Agoda.com, Tiket.com and Booking.com. Based on the results of the interview analysis regarding the strategy of maintaining the quality standards of guest service agent services in hoteli, it still needs to be improved. It can be seen from the four principles proposed by Nasution (2015) regarding Plan, Do, Check, and Action, that the implementation that has been designed to maintain the quality standards of guest service agent services needs to be improved and improved. for this reason, it is hoped that the front office manager and guest service supervisor can manage the work so that the guest service agent staff can work productively and maximize the services provided.